The MAELSTROM-0 Hash Function - Gazzoni Filho, Décio Luiz; Barreto, Paulo S. L. M.; Rijmen, Vincent (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2006: Anais do VI Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2006.20936, 2006)
In this paper we present MAELSTROM-0, an evolution of the WHIRLPOOL hash function with variable output length up to 512 bits. As its predecessor, MAELSTROM-0 is not oriented towards any particular platform, but its implementation flexibility facilitates exploiting the features of each underlying environment. On the other hand, the improved design of MAELSTROM-0 makes it faster and arguably more robust than its predecessor and other existing hash functions. By incorporating the state-of-the-art in the design of cryptographically secure hash functions, MAELSTROM-0 not only constitutes a new primitive per se, but also provides an initial assessment on what the minimum requirements for NIST’s “Advanced Hash Standard” might be, and might serve as a valuable comparison tool for future AHS proposals in terms of security, efficiency, and flexibility.